Dehydration of pili pulp - Ting, Wendy C.
Development of a dried product from pili pulp which is considered a waste product in the pili industry was done in this study. The most acceptable moisture content of the dehydrated product ranged from 11% to 14% and the best method of salting the pulp was determined to be dry salting using 15% salt. The salting step was however effective only in imparting a salty flavor to the product. The reduction in weight attained through this dry salting step was only 7.68%, much less than 50%, which is the usual target i commercial osmotic dehydration. The best temperature for drying salted pili pulp was determined to be 160°F. the dried product had a moisture content ranging from 10.9% to 13.2%, a water activity of 0.458 and an absorbance reading of 0.475 at 420 nm. the general acceptability of the product was described as "liked slightly".